BANGUS CULTURE IN CAGES AT CEBU TECHNOLOGICAL UNIVERSITY SAN FRANCISCO CAMPUS: PROPOSED EXTENSION TRAINING - Dalaguit, Angelo B.; Dalaguit, Mary Ann L; Surbano, Dominador G. (Journal of Agriculture and Technology Management, 2012)
This study determined the viability of Bangus Culture in Cages at Cebu Technological University San Francisco Campus fish farm. This study used sampling techniques and procedures to gather data. Factors considered were average body weight; growth range; mortality; daily feeds requirements and parts per thousand. There were two cages constructed using bamboo frames and nets with a measurement of 7x7x2 meters. The actual number of stocks in cage one were 2,568 pieces while cage two have 1,878 pieces with the salinity average of 35 ppt. within the culture period. The culture period of cage one was 105 days and cage two was 100 days. Seven samplings were done in cage one and six samplings in cage two. The average increment body weight in cage one was 223.7 grams, in cage two, 259.8 grams during harvest. Both were within the standard growth range of 216 -275 grams in 91 - 105 days culture. A mortality rate of 8.81% for cage one which is less than the standard of 10%, assumed to have a survival rate of 90% while cage two have 29.5% mortality within 5 days from stocking period. The daily feeds requirements follows the standard table values of premium feeds. The finding showed that the growth and maturity range in the feeding scheme employed was normally established. Based on the findings, it was concluded that the milkfish culture in cages at Cebu Technological University San Francisco Campus fish farm was suitable. It is recommended to continue the project for further studies, using the same type of formulated feeds to determine financial analysis.